Should I train or should I go? - Georgiadis, Andreas,Kornelakis, Andreas (Global Labor Organization (GLO), 2024)
Extant literature documents a relationship between human resource management (HRM) practices and performance, but the mechanisms underlying this relationship are still not well understood. We develop a theoretical framework of the HRM-performance relationship fusing an employment systems approach with human capital theory and articulating the mechanisms and temporal pathways linking HRM bundles and service quality. We use a unique and large panel dataset from the English social care sector to test our framework. The results highlight the significant role of collective human capital and voluntary turnover in the dynamic relationship between bundles of HRM practices and service quality.
10419/299788
Keywords: Graue Literatur; Human Capital; HR Management; Firm Performance; Turnover; Training